Branch migration based selective PCR for DNA mutation enrichment and detection. Issue 58 (2nd July 2019) - Chen, Na; Ouyang, Xiaofei; Lin, Meng; Liu, Na; Wu, Tongbo; Xiao, Xianjin
Abstract : A selective PCR for the enrichment of low-abundance mutations by introducing a branch migration blocker into the PCR process. Abstract : We presented a branch migration based PCR in which a branch migration blocker was introduced to selectively reduce the amplification efficiency of the wild-type target and enrich the mutant-type target. The low-abundance mutations could be enriched and then detected by high resolution melting, Sanger sequencing or fluorescent DNA probe.